An integrative taxonomy of some close related Palaearctic Macromia spp. (Anisoptera: Macromiidae) - Yu, Xin; Ren, Yanyu; Li, Xinggang; Li, Linyan; Jin, Hongguang (Zootaxa, 2024)
An integrative taxonomy combining morphological and molecular data confirmed that both Macromia amphigena Selys, 1871 and M. manchurica Asahina, 1964 have been assigned to separate species hypotheses, although there is hybridization between the members of these taxa. Scientific names Macromia clio Ris, 1916 and Macromia kubokaiya Asahina, 1964 are shown to be junior synonyms of M. amphigena. Macromia amphigena exhibits a large range of intraspecies morphological variation within its wide distribution, which covers most of East Asia. Macromia berlandi Lieftinck, 1941 is treated as a junior synonym of M. cupricincta Fraser, 1924 based on previous research and the present study. Some traditional diagnostic morphological characters are deemed not suitable for species diagnosis. Integrative taxonomy can help researchers to filter out amphibolous morphological features and find more credible characters for future taxonomy.